Analysis of the Impact of the Development of North Sumatra Sport Center on Sustainable Regional Development in Sena Village, Batang Kuis District, Deli Serdang Regency North Sumatra Province - Torotodo Harefa; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
The sport center is area with complete and adequate sports facilities that accommodate all, sports activities. The north Sumatra North Provincial government is hosting the XXI PON in 2024, even thiught this activity only focuses on sports activities, it has a big impact on social activities in society, the economy and culture. Analysis of construction of a sport center on regional development greatly influences the growth of region with the existence of new regions that become centers of growth, the emergence of regions that become centers of regional growth, among other things, the smoother movement of goods or economic commodities between regions, providing employment opportunities for the population, and can facilitate the increase in community income for micro, small and medium enterprises (MSMEs) to improve the quality of community welfare.